Cultural politics of enterprise lending and controls in closely held banks: A case study from Sri Lanka. Issue 4 (7th November 2016) - Saliya, Candauda Arachchige; Jayasinghe, Kelum
Abstract : Purpose: The purpose of this paper is to focus on the enterprise lending and control process in closely held banks, with special reference to Sri Lanka. It explores how those processes are being influenced by the distinctive cultural and political processes at organizational and societal levels. Design/methodology/approach: The study relies on three cases built upon the life experiences of several employees in a closely held bank, articulating multiple sources of evidence: interviews, observations, documents, archival records, open-ended questionnaires, internet conversations and exchange of e-mails. The data analysis adopts cultural political economy theory. Findings: The study's findings reveal how cultural and political factors, such as egoistic motives and politics, gifts/rewards and a manipulative culture, along with exploitative and discriminatory politics at organizational and societal levels, articulate into the enterprise lending and control process ("five Cs") in closely held banks. "Rational" enterprise lending and control processes in this context merely become a "ceremonial" practice, serving the petty interest of powerful capitalist business owners. Whereas previous studies emphasize that the criteria (five Cs) discriminate against ordinary people, as distinct from the élite, the findings of this study implicate that over and above that the criteria are set aside when it suits in order to favor or accommodate the élite. Originality/value: The paper provides a "qualitative inquiry" on how cultural politics at organizational and societal-level effect on enterprise lending and control process within closely held banks in less developed countries (LDCs). The previous studies on bank lending and control used either large-scale surveys or alternatively devoted their interest toward the role and impact of accounting in World Bank and IMF-led lending schemes and policies, particularly in LDCs.